Bridging Indonesia’s Digital Divide: Rural-Urban Linkages? - Aulia Hadi (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2018)
While Indonesia is recorded as one of the greatest social media republics in the world, the gap of rural-urban internet access remains a great challenge. As reported in the 2016 Information and Communication Technology (ICT) Indicators, the number of households with internet access in rural areas is nearly half of those in urban areas; 26.3% and 48.5% in a consecutive way. Rather than simply seeing the internet as a medium, this paper discusses the internet as material culture; therefore, it goes beyond the access and focuses on the ways people use the internet to define their culture. From this perspective, this paper draws the two levels of the digital divide of Indonesian rural-urban dwellers. Lack of motivation and limited material access due to social inequality is at the very base of the digital divide. Subsequently, digital skills and usage deepen the digital divide. While splitting people into either rural or urban categories often produces misleading policies, this paper proposes the rural-urban linkages to bridge the digital divide in Indonesia. The rural-urban linkages particularly incorporate the flow of people and information across space as well as the interconnection between sectors, such as agriculture and service.